Preparation method of high-voltage electrolytic capacitor diaphragm with high liquid absorbency
By using high-purity insulated needle wood pulp and using continuous drying process, the problem of poor liquid absorption of the separator of high-voltage electrolytic capacitors is solved, and the consideration of high liquid absorption and low internal resistance is achieved.
Patent Information
- Application Number
- CN202510416878.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-06-10
AI Technical Summary
While the existing high-voltage electrolytic capacitor diaphragms increase the withstand voltage, poor liquid suction properties lead to high internal resistance, making it difficult to meet the dual requirements of high liquid suction properties and low internal resistance.
High-purity insulated needle wood pulp is used for beating and long mesh forming. Through continuous drying methods of heating and cooling and decompression drying, a high-liquid absorbing high-voltage electrolytic capacitor separator is formed.
While maintaining high voltage resistance, the liquid absorption performance of the diaphragm is significantly improved, the ion movement resistance is reduced, and the internal resistance of the diaphragm is reduced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of papers for aluminum electrolytic capacitors, and particularly to a method for preparing a high liquid-absorbing high-voltage electrolytic capacitor separator. Background Art
[0002] Electrolytic capacitors are one of the important components in the electronics industry. In addition to filtering, decoupling, and signal coupling in circuits, they also play special roles in special circuits such as correction circuits, power supply circuits, and AC motor starting circuits. They are widely used in fields such as the automotive industry, security industry, medical electronics, computers and TVs, electronic toys, and industrial control.
[0003] The electrolytic capacitor separator mainly plays the roles of isolating the positive and negative electrodes and adsorbing the electrolyte in the electrolytic capacitor. It can be divided into a high-voltage electrolytic capacitor separator and a low-voltage electrolytic capacitor separator according to the usage requirements. The high-voltage electrolytic capacitor separator is required to have high voltage resistance performance; the low-voltage electrolytic capacitor separator has low requirements for voltage resistance, but requires the paper to have good absorbability and low internal resistance. With the development of technology, higher requirements are put forward for the high-voltage electrolytic capacitor separator, which not only requires high voltage resistance but also low internal resistance. And the quality of the liquid absorption of the separator directly affects the level of the internal resistance of the capacitor. Therefore, the most direct method to reduce the internal resistance of the capacitor is to improve its liquid absorption performance.
[0004] Generally, the diaphragms of high-voltage electrolytic capacitors are made of plant fibers and have a relatively high beating degree to ensure the compactness of the diaphragms, thus having high breakdown voltage resistance. However, if the beating degree is too high, a large number of hydrogen bonds are formed by the hydroxyl groups on the diaphragm surface, and the number of free hydroxyl groups on the diaphragm surface decreases, resulting in very poor liquid absorption performance of the diaphragm, reduced amount of adsorbed electrolyte, and ultimately a relatively high internal resistance. Patent CN201510359165.2 discloses a high-voltage-resistant electrolytic capacitor paper and its preparation method. This product is obtained by compounding low-density cotton pulp and / or hemp pulp with high-density insulating wood pulp and then coating. Due to the presence of a low-density layer, it is difficult to achieve a very high breakdown voltage for the product at the same thickness. Patent CN201810006288.1 discloses a breakdown voltage-resistant electrolytic capacitor paper and its preparation method. This product is obtained by compounding low-density sisal pulp with high-density sisal pulp and then coating. Due to the presence of a low-density layer, it is also difficult to achieve a very high breakdown voltage for the product at the same thickness. Patent CN201811448628.2 discloses a breakdown-resistant composite electrolytic capacitor paper and its production method. This product consists of a breakdown voltage-resistant layer and an absorption layer. The slurry of the breakdown voltage-resistant layer includes insulating wood pulp and nanofibrillated cellulose, and the slurry of the absorption layer includes hemp pulp, cotton pulp, and straw pulp. Then, the breakdown voltage-resistant layer and the absorption layer are compounded through a long cylinder screen to finally obtain the product. Since this product also contains a low-density layer, the breakdown voltage per unit thickness is still not high. Patent CN2023118186771 discloses a preparation method of a high-voltage and low-loss electrolytic capacitor diaphragm. The surface of this diaphragm is treated with plasma to improve the liquid absorption performance of the diaphragm and reduce the internal resistance of the diaphragm. However, after the diaphragm is treated with plasma, as the placement time of the diaphragm extends, the liquid absorption effect will gradually decrease. At the same time, during the process of preparing the diaphragm into a capacitor, it also needs to be dried at a high temperature. The high-temperature treatment will significantly reduce the liquid absorption performance of the diaphragm, ultimately resulting in a decrease in the liquid absorption property of the diaphragm and an increase in the internal resistance, so its practical use is restricted to a certain extent. Patent CN202210393452.5 discloses an inorganic hybrid aramid nanofiber diaphragm. In this patent, the aramid nanofiber dispersion is placed in a petri dish with a diameter of 20 cm and dried in a hot air oven at 80 °C for 2 hours. Then, after standing at room temperature for 2 h, it is further vacuum freeze-dried for 4 hours to obtain a pure nanofiber aramid fiber lithium-ion battery diaphragm. Summary of the Invention
[0005] Aiming at the deficiencies of the prior art, the present invention provides a preparation method of a high-liquid-absorption high-voltage electrolytic capacitor diaphragm. It is not necessary to prepare by combining a breakdown voltage-resistant layer and an absorption layer, which can not only retain the high breakdown voltage resistance of the diaphragm but also greatly improve the liquid absorption performance of the diaphragm, thereby reducing the ion migration resistance and lowering the internal resistance of the diaphragm.
[0006] To achieve the above objectives, the present invention adopts the following technical solutions: A preparation method of a separator for a high liquid-absorbing high-voltage electrolytic capacitor, the preparation method comprising the following steps: 1) High-purity insulating coniferous wood pulp is beaten using a disk refiner to obtain insulating coniferous wood pulp with a beating degree of 88°SR to 98°SR; 2) The above-mentioned insulating coniferous wood pulp is formed by a fourdrinier former, and then heated and dried through a first group of drying cylinders to obtain a wet paper web A, and the moisture content of the wet paper web A is 30% to 50%; 3) The wet paper web A is further frozen through a second group of freezing cylinders to obtain a wet paper web B; 4) The wet paper web B enters a decompression chamber and is dried using a third group of freezing cylinders, exits the decompression chamber after drying, and then is calendered to obtain a separator for a high liquid-absorbing high-voltage electrolytic capacitor; The first group of drying cylinders, the second group of freezing cylinders, and the third group of freezing cylinders each include a plurality of cylinders; wherein, the lowest surface temperature of the first group of drying cylinders is 25°C to 40°C, the highest surface temperature is 45°C to 70°C, and the surface temperature of each drying cylinder is not lower than the surface temperature of the previous drying cylinder; the lowest surface temperature of the second group of freezing cylinders is -45°C to -55°C, the highest surface temperature is -15°C to -25°C, and the surface temperature of the freezing cylinders as a whole decreases first and then increases; the lowest surface temperature of the third group of freezing cylinders is -15°C to -10°C, the highest surface temperature is 0°C to 2°C, and the surface temperature of the freezing cylinders as a whole gradually increases from low to high.
[0007] Preferably, the beating consistency of the insulating coniferous wood pulp is 3% to 6%.
[0008] Preferably, the forming consistency of the insulating coniferous wood pulp is 0.2% to 0.8%.
[0009] Preferably, the number of drying cylinders in the first group of drying cylinders is 3 to 8, and the surface temperature of each drying cylinder is 30°C to 50°C.
[0010] Preferably, the first group of drying cylinders is 5 drying cylinders, and the surface temperatures of the drying cylinders are 40°C, 45°C, 45°C, 50°C, 50°C or 30°C, 30°C, 40°C, 40°C, 45°C respectively.
[0011] Preferably, the number of freezing cylinders in the second group of freezing cylinders is 3 to 8, and the surface temperature of each freezing cylinder is -50°C to -20°C.
[0012] Preferably, the number of freezing cylinders in the second group of freezing cylinders is 5, and the surface temperatures of the freezing cylinders are -20°C, -40°C, -50°C, -50°C, -30°C.
[0013] Preferably, the number of freezing cylinders in the third group of freezing cylinders is 15 to 25, and the surface temperature of each freezing cylinder is -10°C to 0°C.
[0014] The number of the freezing cylinders in the third group is 20, and the surface temperatures of each freezing cylinder are -10°C, -10°C, -8°C, -8°C, -8°C, -6°C, -6°C, -6°C, -4°C, -4°C, -4°C, -4°C, -2°C, -2°C, -2°C, -2°C, 0°C, 0°C, 0°C, 0°C.
[0015] Preferably, the vacuum degree of the decompression chamber is 50 kPa to 98 kPa; more preferably, the vacuum degree of the decompression chamber is 80 kPa to 98 kPa.
[0016] Preferably, the contact time between the paper web and each cylinder is 0.3 s to 3 s.
[0017] Furthermore, the present invention also provides a highly absorbent high-voltage electrolytic capacitor separator prepared by the preparation method described above.
[0018] All the separators of the present invention are prepared from highly beaten and highly pure insulating softwood pulp, which can ensure a relatively high breakdown voltage per unit thickness. And the adopted preparation method is a continuous drying method, and the drying efficiency is higher than that of the intermittent drying method. After the fibers are formed by a long wire, first warm drying is adopted, and then freeze-vacuum drying is adopted, which can effectively increase the fine pore structure between the fibers, not only retain the high breakdown voltage of the separator, but also greatly improve the liquid absorption performance of the separator, thereby reducing the ion migration resistance and lowering the internal resistance of the separator. Specific Embodiments
[0019] Combined with the embodiments of the present invention below, the technical solutions in the embodiments will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts shall fall within the protection scope of the present invention.
[0020] Reference Example 1 The highly pure insulating softwood pulp is beaten by a disk refiner, the beating degree is 92°SR, the beating consistency is 5%, the beaten pulp is dispersed in water, fed into the paper machine headbox system, formed by a long wire, the forming consistency is 0.4%, and the papermaking process is carried out according to the conventional process for dehydration forming, pressing, drying, then calendering and winding, and the detection indexes are measured.
[0021] Reference Example 2 The highly pure insulating softwood pulp is beaten by a disk refiner, the beating degree is 96°SR, the beating consistency is 5%, the beaten pulp is fed into the paper machine headbox system, formed by a long wire, the forming consistency is 0.4%, and the papermaking process is carried out according to the conventional process for dehydration forming, pressing, drying, then calendering and winding, and the detection indexes are measured.
[0022] Example 1 High-purity insulating coniferous wood pulp is beaten with a disc refiner. The beating degree is 92°SR and the beating consistency is 5%. After beating, it is sent to the paper machine headbox system and formed on a fourdrinier wire with a forming consistency of 0.4%. Then it passes through the first group of drying cylinders #1-#5 for heating and drying. The surface temperatures of cylinders #1-#5 are 40°C, 45°C, 45°C, 50°C, and 50°C respectively. After drying, a wet paper web A is obtained with a moisture content of 35%. Then it passes through the second group of freezing cylinders #6-#10. The surface temperatures of cylinders #6-#10 are -20°C, -40°C, -50°C, -50°C, and -30°C respectively. Then it enters a decompression chamber with a vacuum degree of 80 kPa. The surface temperatures of the third group of freezing cylinders #11-#30 in the decompression chamber are -10°C, -10°C, -8°C, -8°C, -8°C, -6°C, -6°C, -6°C, -4°C, -4°C, -4°C, -4°C, -2°C, -2°C, -2°C, -2°C, 0°C, 0°C, 0°C, and 0°C respectively. The contact time of the paper web with each cylinder is 0.5 s. After leaving the decompression chamber, it is calendered and wound up for inspection of indicators.
[0023] Example 2 High-purity insulating coniferous wood pulp is beaten with a disc refiner. The beating degree is 92°SR and the beating consistency is 5%. After beating, it is sent to the paper machine headbox system and formed on a fourdrinier wire with a forming consistency of 0.4%. Then it passes through the first group of drying cylinders #1-#5 for heating and drying. The surface temperatures of cylinders #1-#5 are 40°C, 45°C, 45°C, 50°C, and 50°C respectively. After drying, a wet paper web A is obtained with a moisture content of 45%. Then it passes through the second group of freezing cylinders #6-#10. The surface temperatures of cylinders #6-#10 are -20°C, -40°C, -50°C, -50°C, and -30°C respectively. Then it enters a decompression chamber with a vacuum degree of 95 kPa. The surface temperatures of the third group of freezing cylinders #11-#30 in the decompression chamber are -10°C, -10°C, -8°C, -8°C, -8°C, -6°C, -6°C, -6°C, -4°C, -4°C, -4°C, -4°C, -2°C, -2°C, -2°C, -2°C, 0°C, 0°C, 0°C, and 0°C respectively. The contact time of the paper web with each cylinder is 0.5 s. After leaving the decompression chamber, it is calendered and wound up for inspection of indicators.
[0024] Example 3 High-purity insulating coniferous pulp is beaten with a disc refiner, the beating degree is 96°SR, and the beating consistency is 5%. After beating, it is sent to the paper machine headbox system, formed on a Fourdrinier wire, and the forming consistency is 0.4%. Then it is dried by heating with the first group of cylinders #1 - #5, and the surface temperatures of cylinders #1 - #5 are 30°C, 30°C, 40°C, 40°C, and 45°C respectively. After drying, a wet paper web A is obtained, and the moisture content of wet paper web A is 32%. Then it passes through the second group of cylinders #6 - #10, and the surface temperatures of cylinders #6 - #10 are -20°C, -40°C, -50°C, -50°C, and -30°C respectively. Then it enters a decompression chamber, and the vacuum degree of the decompression chamber is 80 kPa. The surface temperatures of the third group of cylinders #11 - #30 in the decompression chamber are -10°C, -10°C, -8°C, -8°C, -8°C, -6°C, -6°C, -6°C, -4°C, -4°C, -4°C, -4°C, -2°C, -2°C, -2°C, -2°C, 0°C, 0°C, 0°C, and 0°C respectively. The contact time of the paper web with each cylinder is 0.5 s. After leaving the decompression chamber, it is calendered and wound up for inspection of indicators.
[0025] Example 4 High-purity insulating coniferous pulp is beaten with a disc refiner, the beating degree is 96°SR, and the beating consistency is 5%. After beating, it is sent to the paper machine headbox system, formed on a Fourdrinier wire, and the forming consistency is 0.4%. Then it is dried by heating with the first group of cylinders #1 - #5, and the surface temperatures of cylinders #1 - #5 are 30°C, 30°C, 40°C, 40°C, and 45°C respectively. After drying, a wet paper web A is obtained, and the moisture content of wet paper web A is 42%. Then it passes through the second group of cylinders #6 - #10, and the surface temperatures of cylinders #6 - #10 are -20°C, -40°C, -50°C, -50°C, and -30°C respectively. Then it enters a decompression chamber, and the vacuum degree of the decompression chamber is 90 kPa. The surface temperatures of the third group of cylinders #11 - #30 in the decompression chamber are -10°C, -10°C, -8°C, -8°C, -8°C, -6°C, -6°C, -6°C, -4°C, -4°C, -4°C, -4°C, -2°C, -2°C, -2°C, -2°C, 0°C, 0°C, 0°C, and 0°C respectively. The contact time of the paper web with each cylinder is 0.5 s. After leaving the decompression chamber, it is calendered and wound up for inspection of indicators.
[0026] Comparative Example 1 High-purity insulating coniferous pulp is beaten with a disc refiner, the beating degree is 92°SR, and the beating consistency is 5%. After beating, it is sent to the paper machine headbox system, formed on a Fourdrinier wire, and the forming consistency is 0.4%. Then it is dried in a hot air oven at 80°C for 2 hours, then left standing at room temperature for 2 h, and then vacuum freeze-dried for 4 hours. After that, it is calendered and wound up for inspection of indicators.
[0027] All kinds of raw materials, reagents, instruments, and equipment used in the present invention can be obtained through market purchase or can be prepared by existing methods. The detection methods in the above reference examples and examples are as follows: Bulk density: GB / T 451.3; Thickness: GB / T 451.3; Breakdown voltage: GB / T 12913; Height of water absorption: GB / T 461.1.
[0028] The test results are shown in Table 1.
[0029] Table 1 It can be seen from Table 1 that Example 4 has the best comprehensive performance. By comparing Reference Example 1 with Examples 1 and 2, and Reference Example 2 with Examples 3 and 4, it can be seen that the preparation method of the present invention can significantly improve the liquid absorption performance of the separator without affecting the high breakdown voltage, thickness, and bulk density of the separator, thereby reducing the ion migration resistance and the internal resistance of the separator. It can be seen from Example 1 and Comparative Example 1 that the preparation method of Comparative Example 1 has no obvious effect on improving the liquid absorption performance of the separator and takes a long time, while the present invention can effectively improve the liquid absorption performance of the separator and takes a short time.
[0030] The above is the description of the embodiments of the present invention. Through the above description of the disclosed embodiments, those skilled in the art can implement or use the present invention. Various modifications to these embodiments will be obvious to those skilled in the art. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to these embodiments shown herein, but will be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a high-liquid-absorbent high-voltage electrolytic capacitor diaphragm, characterized in that: The preparation method comprises the following steps: 1) High-purity insulating coniferous pulp is beaten by a disc refiner to obtain insulating coniferous pulp with a beating degree of 88°SR~98°SR; 2) The insulating coniferous wood pulp is formed by a fourdrinier wire, and then passed through a first set of drying cylinders for heating and drying to obtain a wet paper web A, wherein the moisture content of the wet paper web A is 30-50%; 3) The wet paper web A is then frozen by the second set of freezing cylinders to obtain wet paper web B; 4) The wet paper web B enters the decompression chamber and is dried by the third group of freezing cylinders. After drying, it exits the decompression chamber and is calendered to obtain a high-liquid-absorbent high-voltage electrolytic capacitor diaphragm; The first group of drying cylinders, the second group of freezing cylinders and the third group of freezing cylinders all include multiple cylinder bodies; among them, the surface temperature of the first group of drying cylinders has a minimum temperature of 25°C~40°C and a maximum temperature of 45°C~70°C, and the surface temperature of each drying cylinder is not lower than the surface temperature of the previous drying cylinder; the surface temperature of the second group of freezing cylinders has a minimum temperature of -45°C~-55°C and a maximum temperature of -15°C~-25°C, and the surface temperature of the freezing cylinders increases from high to low as a whole; the surface temperature of the third group of freezing cylinders has a minimum temperature of -15°C~-10°C and a maximum temperature of 0°C~2°C, and the surface temperature of the freezing cylinders increases gradually from low to high as a whole.
2. The preparation method according to claim 1, characterized in that: The beating concentration of the insulating coniferous pulp is 3% to 6%; and / or the forming concentration of the insulating coniferous pulp is 0.2% to 0.8%.
3. The preparation method according to claim 1, characterized in that: The number of drying cylinders in the first group of drying cylinders is 3 to 8, and the surface temperature of the first group of drying cylinders is 30° C. to 50° C.
4. The preparation method according to claim 3, characterized in that: The first group of drying cylinders consists of 5 drying cylinders, and the surface temperatures of the drying cylinders are 40°C, 45°C, 45°C, 50°C, 50°C or 30°C, 30°C, 40°C, 40°C, 45°C respectively.
5. The preparation method according to claim 1, characterized in that: The number of freezing cylinders in the second group of freezing cylinders is 3 to 8, and the surface temperature of each freezing cylinder is -50°C to -20°C.
6. The preparation method according to claim 5, characterized in that: The number of freezing cylinders in the second group of freezing cylinders is 5, and the surface temperatures of the freezing cylinders are -20°C, -40°C, -50°C, -50°C, and -30°C.
7. The preparation method according to claim 1, characterized in that: The number of freezing cylinders in the third group of freezing cylinders is 15 to 25, and the surface temperature of each freezing cylinder is -10°C to 0°C.
8. The preparation method according to claim 7, characterized in that: The number of freezing cylinders in the third group of freezing cylinders is 20, and the surface temperature of each freezing cylinder is -10℃, -10℃, -8℃, -8℃, -8℃, -6℃, -6℃, -4℃, -4℃, -4℃, -2℃, -2℃, -2℃, 0℃, 0℃, 0℃, 0℃, 0℃.
9. The preparation method according to claim 1, characterized in that: The vacuum degree of the decompression chamber is 50 kPa to 98 kPa; and / or the contact time between the paper web and each cylinder is 0.3S to 3S.
10. A high-liquid-absorbent high-voltage electrolytic capacitor diaphragm prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
High voltage resistant electrolytic capacitor paper and preparation method thereof
CN104988809A
Voltage withstanding electrolytic capacitor paper and preparation method thereof
CN108221485A
A breakdown-resistant composite electrolytic capacitor paper and its production method
CN109722945B
Inorganic hybridized aramid nanofiber diaphragm, preparation method and application of inorganic hybridized aramid nanofiber diaphragm in lithium battery
CN114725616A
Cited By
Preparation method of electrolytic capacitor paper with high liquid absorbency
CN122169383A
A micro-nano fiber regulated liquid aluminum electrolytic capacitor diaphragm and a preparation method thereof
CN122658894A